単離ミトコンドリアを含む関節リウマチの予防または治療のための医薬組成物 (2022)
【課題】本発明は、関節リウマチの予防または治療のための医薬組成物を提供し、さらに詳しくは、関節リウマチの予防または治療のための有効成分としてミトコンドリアを含む医薬組成物を提供する。【解決手段】本発明の外因性ミトコンドリア医薬組成物は、関節リウマチに罹患している対象に投与されると、対象は浮腫および紅斑症状を緩和することができる。さらに、本発明の医薬組成物は、炎症性サイトカインIL-6の発現レベルを低下させるが、対象における抗炎症性サイトカインIL-10の発現レベルを増加させる。したがって、本発明の医薬組成物は、関節リウマチの予防または治療に有効に使用することができる。【選択図】なし The present invention relates to a pharmaceutical composition for prevention or treatment of rheumatoid arthritis and, more particularly, to a pharmaceutical composition compsiring mitochondria as an effective ingredient for prevention or treatment of rheumatoid arthritis. When a foreign mitochondria pharmaceutical composition of the present invention is administered to a subject suffering from rheumatoid arthritis, the subject may alleviate edema and rubefaction symptoms. In addition, the pharmaceutical composition of the present invention reduces an expression level of the inflammatory cytokine IL-6, but increases an expression level of the anti-inflammatory cytokine IL-10 in the subject. Therefore, the pharmaceutical composition according to the present invention can be effectively used for preventing or treating rheumatoid arthritis.